MDL-800, an allosteric activator of SIRT6, suppresses proliferation and enhances EGFR-TKIs therapy in non-small cell lung cancer - Shang, Jia-lin (Acta Pharmacol Sin, 2020)
Sirtuin 6 (SIRT6), a member of the sirtuin family, is a nicotinamide adenine dinucleotide (NAD(+))-dependent deacetylase that is involved in various physiological and pathological processes. SIRT6 is generally downregulated and linked to tumorigenesis in non-small cell lung carcinoma (NSCLC), thus regarded as a promising therapeutic target of NSCLC. In this study, we investigated whether MDL-800, an allosteric activator of SIRT6, exerted antiproliferation effect against NSCLC cells in vitro and in vivo. We showed that MDL-800 increased SIRT6 deacetylase activity with an EC(50) value of 11.0 ± 0.3 μM; MDL-800 (10–50 μM) induced dose-dependent deacetylation of histone H3 in 12 NSCLC cell lines. Treatment with MDL-800 dose dependently inhibited the proliferation of 12 NSCLC cell lines with IC(50) values ranging from 21.5 to 34.5 μM. The antiproliferation effect of MDL-800 was significantly diminished by SIRT6 knockout. Treatment with MDL-800 induced remarkable cell cycle arrest at the G(0)/G(1) phase in NSCLC HCC827 and PC9 cells. Furthermore, MDL-800 (25, 50 μM) enhanced the antiproliferation of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in osimertinib-resistant HCC827 and PC9 cells as well as in patient-derived primary tumor cells, and suppressed mitogen-activated protein kinase (MAPK) pathway. In HCC827 cell-derived xenograft nude mice, intraperitoneal administration of MDL-800 (80 mg · kg(−1) · d(−1), for 14 days) markedly suppressed the tumor growth, accompanied by enhanced SIRT6-dependent histone H3 deacetylation and decreased p-MEK and p-ERK in tumor tissues. Our results provide the pharmacological evidence for future clinical investigation of MDL-800 as a promising lead compound for NSCLC treatment alone or in combination with EGFR-TKIs.